Influence of photovoltaic generation model and time resolution on the reliability evaluation of distribution systems. (10th September 2020) - de Oliveira, Ricardo; Borges, Carmen L. T.
Summary: This paper aims to investigate the influence of photovoltaic (PV) generation on reliability evaluation of distribution systems. Two PV generation models are used to predict the output power injected into the grid, taking into account the main relevant environmental variables, the irradiance and ambient temperature. Issues that directly affect the output power, such as the spatial smoothing effect due to the plant size and the influence of the irradiance and temperature measurement interval are taken into consideration. Using measurement time series of irradiance and local temperature, the models are used to generate power series in 4‐minute and hourly resolutions. The generated power series are used in a reliability assessment model, with the objective of evaluating the impact of solar resource variability on the reliability indices of the system. Case studies on the IEEE RBTS‐Bus 2 and on the real distribution system of Fernando de Noronha in Brazil are presented and discussed, for power plants of different capacities, considering the effect of the PV generation models, the temporal resolution of the time series and the spatial smoothing of the power output fluctuations. The results show that the power time series in hourly resolution significantly underestimates the frequency of interruptions. For the real system, this index is underestimated at the system level (up to 43%) and at the load points (up to 72%). On the other hand, for the interruption duration index, the temporal aggregation results in a small underestimation (just 4%). The results also indicates that the smoothing effect is irrelevant for typical PV system sizes of distribution systems with discretization equal to or above 4 minutes. Abstract : Two photovoltaic generation models used to estimate the output power taking into account irradiance, temperature and measurement interval, and the output series used to calculate and compare reliability indices. In a network with high reliability level, the temperature and temporal aggregation has small effect on the indices. But in general, the temperature effect is to reduce the power generated and increase significantly the load shedding frequency index, while spatial smoothing effect may be neglected for plants up to 5 MWp.